Principles of Good Governance in Quranic’s Perspective - Eko Sudarmanto; Triana Zuhrotun Aulia (International Journal of Islamic Thought and Humanities, 2022)
The purpose of this study is to find out how the Quran perspectives in explaining the principles of good governance. The methodology used in this research is library research through a qualitative approach , namely research that processes thinking deductively and inductively. The source of this research data consists of a primary data source in the form of Verses of the Qur'an which is used as a reference with the explanation of several mufasir, and a secondary data source consisting of relevant previous scientific research works in the form of books, journals and other scientific works. The metode of the Interpretation of Al-Quran used as a method of analysis in this study is the method of tafsir al-maudhu'i. In conclusion, some contextual principles in good governance are contained in several verses in the Qur'an, both on Transparency, Accountability, Responsibility, Independentity, and Fairness. The important point of this research is that in offering a solution to a problem, Al-Quran always provides perspective not only materially but also a spiritual perspective.